The interview challenge: Mike Simmen versus the FBI. - Einspahr, Owen (FBI Law Enforcement Bulletin, 2000)
Law enforcement officers can now enhance their most fundamental and important skill, interviewing individuals, using an interactive computer program that closely imitates real life. Interviewing instructors at the FBI Academy worked together with members of the Johns Hopkins University's Applied Physics Laboratory to create a computer program that would realistically simulate a human personality. They developed a self-paced, multimedia computer program that can provide law enforcement professionals with realistic interviewing practice. The software gives both veteran officers and students experience in asking appropriate questions and distinguishing between deceptive and truthful responses. The program provides a critique and a numerical score, so that users can compare their level of improvement. This program demonstrates how modern technology can be used to assist officers in their daily struggle to solve crimes and safeguard communities. Details of the program and its use are provided.